Injectable hydrogel loaded with bilayer microspheres to inhibit angiogenesis and promote cartilage regeneration for repairing growth plate injury - Qiang, Lei; Fan, Minjie; Wang, Yiwei; Liu, Yihao; Zhuang, Hanjie; Guo, Ruoyi; Huang, Hao; Ben, Yulong; Wang, Dalin; Wu, Xiaoling; Wang, Jinwu; Weng, Jie; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
The repair and regeneration of growth plate injuries using tissue engineering techniques remains a challenge due to large bone bridge formation and low chondrogenic efficiency. In this study, a bilayer drug-loaded microspheres was developed that contains the vascular endothelial growth factor (VEGF) inhibitor, Bevacizumab, on the outer layer and insulin-like growth factor-1 (IGF-1), a cartilage repair factor, on the inner layer. The in vitro drug-release profile of bilayer microspheres showed a sequential release, with Bevacizumab released first followed by IGF-1. The microspheres were then combined with bone marrow mesenchymal stem cells (BMSCs) in the gelatin methacryloyl (GelMA) hydrogel to create a composite hydrogel with good injectability and biocompatibility. And this hydrogel simultaneously inhibited angiogenesis and promoted cartilage regeneration. Finally, in vivo studies indicated that the composite hydrogel reduced bone bridge formation and improved cartilage regeneration in the rabbit model of proximal tibial growth plate injury. This bilayer microsphere-based composite hydrogel with sequential controlled release of Bevacizumab and IGF-1 has promising potential for growth plate injury repair.